Analisis Kerusakan Dan Estimasi Biaya Rehabilitasi Bangunan Gedung Rusunawa Universitas Palangka Raya - Wati, Elna; Nuswantoro, Waluyo (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
Due to problems in licensing during the construction process, as a result the rusunawa building cannot be operated until now. So that the rusunawa building became abandoned and suffered a lot of damage. This article aims to identify damage, estimate rehabilitation costs and determine the priority of handling the estimated rehabilitation costs. The method used is direct observation. The research was conducted for three months from January to March 2024. The results showed that the damage that occurred was rusty roof tiles, rusty ridges, weathered lisplank, loose gutters, peeling and faded wall paint, damaged door and window frames, loose door leaves, damaged window leaves and broken glass, rusty door hinges, rusty door hinges, rusty window hinges, rusty door locks, rusty door latches, rusty window latches, cracked and loose floor tiles, moldy and leaking ceilings, missing water faucets, loose floor drains, missing fire hydrants, loose light fittings and lamps, loose fire alarms. The estimated cost of rehabilitation of damage to the Palangka Raya University Rusunawa building is Rp.1,710,825,000.00. Priority handling of the estimated cost of rehabilitation of architectural components, namely door leaves amounting to Rp.438,029,305.96. Mechanical components, namely fire hydrants amounting to Rp.54,645,755.10. Electrical components, namely fire alarms amounting to Rp.33,092,398.92